A Giant Parathyroid Tumor during Pregnancy: Adenoma versus Carcinoma - Rusella Mirza; Eric X. Wei (Hindawi Limited, 2019)
Primary hyperparathyroidism (PHP) is one of the most common endocrine diseases. However, it is rare during pregnancy. 85% cases of the PHP are due to parathyroid adenoma (PA) and less than 1% because of parathyroid carcinoma (PC). Here we report a case of giant parathyroid adenoma (GPA) in a patient with first trimester pregnancy. Her calcium and parathyroid hormone (PTH) levels were very high. The tumor measured 5 cm in greatest dimension, weighed 37 grams, and was adherent to the surrounding tissues. Grossly, the tumor was encapsulated and composed of solid and cystic components. Cut surface was reddish brown and soft. Microscopically, the tumor had a thick irregular capsule with entrapped parathyroid cells and extensive foreign body type reactions. The tumor was composed of multiple cell types with areas of pleomorphism. The mitotic index was nonetheless low. Even though the tumor was large and adherent with the surrounding strap muscles, the gross appearance and the histological morphology favored benign parathyroid adenoma. In this paper, we have discussed some important differential aspects of GPA, PA, and PC.